Detection of dengue virus from field-captured Aedes albopictus in Seberang Takir, Kuala Nerus, Terengganu, Malaysia - Lee, Chia Hau; Norasmah Basari,; Suzana Misbah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Dengue is an arthropod-borne disease caused by dengue virus (DENV) infection. The virus is transmitted to humans through the bite of Aedes mosquito. Seberang Takir of Kuala Nerus, Terengganu, had been identified as one of dengue hotspots representing a large number of dengue cases in 2016. This study aimed to screen for the presence of DENV in Aedes species of Seberang Takir and to estimate the viral infection in mosquitoes through minimum infection rate (MIR) and maximum likelihood estimation (MLE). Mosquitoes were caught using carbon dioxide-baited trap, attractive sugar bait trap and human landing catches (HLC) from October 2016 to January 2017. HLC was found to be the most efficient mosquito collecting method yielding 1151 individuals. Out of these, 337 mosquitoes belonged to Aedes albopictus, representing 334 females and 13 males. DENV was screened from these mosquitoes using reverse transcriptase-polymerase chain reaction. Interestingly, two out of 15 mosquito pools (7 females per pool) were found positive for DENV, whereas the remaining pools were shown to be negative for the virus detection. This reveals a MIR 19.05 and MLE 20.24 per 1,000 mosquitoes, which indicates a potential risk of dengue transmission in Seberang Takir. Detection of DENV in A. albopictus females is alarming, which requires rigorous vector control in order to prevent severe dengue outbreaks in the future.